PEMEROLEHAN HASIL BELAJAR KEMAMPUAN MEMBACA BAHASA INDONESIA SISWA KELAS V SDN 18 SIMALEGI SIBERUT BARAT KABUPATEN KEPULAUAN MENTAWAI - Gusnetti; Marsis; Naini, Ineng; Fia Afriani (Cerdas Proklamator, 2024)
Obtaining learning outcomes for the ability to read Indonesian using the Student Team Achievement Division (STAD) model in class V of SDN 18 Simalegi West Siberut, Mentawai Islands Regency is the result of research in the Even Semester of the 2022/2023 academic year. The theory used in this research is about language skills by Sanjaya (2011), reading by Dalman (2013) and Gusnetti (2018), the STAD model by Oktavia (2020) and Rusman (2011). Classroom Action Research (PTK) was used in this research to obtain data, focused on class V students at SDN 18 Simalegi, West Siberut District with a total of 36 people. In carrying out the research, 2 cycles were carried out. The research results are: (1) the percentage of teacher activity increased from 72.5% to 87.5%. (2) the percentage of students' learning activities increased from 59.7% to 83.32%. (3) student learning outcomes increased from 69.44% to 94.44%. It can be concluded that by using the Student Team Achievement Division (STAD) model, there was an increase in learning outcomes for reading ability in Indonesian language learning in class V of SDN 18 Simalegi, Mentawai Islands Regency.